The extraordinary AFD thermosensor of C. elegans - Goodman, Miriam B. (Pflugers Arch, 2017)
The nematode C. elegans exhibits complex thermal experience-dependent navigation behaviors in response to environmental temperature changes of as little as 0.01°C over a >10°C temperature range. The remarkable thermosensory abilities of this animal are mediated primarily via the single pair of AFD sensory neurons in its head. In this review, we describe the contributions of AFD to thermosensory behaviors and temperature-dependent regulation of organismal physiology. We also discuss the mechanisms that enable this neuron type to adapt to recent temperature experience and to exhibit extraordinary thermosensitivity over a wide dynamic range.